Pengaruh Transfer Pricing Perusahaan Induk dan Cabang Skala Multinasional pada PT Toyota Motor Manufacturing Indonesia - Nurhasanah, Ayu; Purwanti, Purwanti; Puspita, Wati Della (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this study is to analyze the transfer pricing practices carried out by PT Toyota Motor Manufacturing Indonesia (TMMIN), a subsidiary of Toyota Motor Corporation Japan, and its impact on tax obligations in Indonesia. The method used is a qualitative descriptive approach through case studies, through data collection techniques with literature studies and documentation. The results of the study indicate that TMMIN is involved in affiliate transactions that are not in accordance with the arm's length principle, such as sales at prices below market and the imposition of royalties that should not be. This practice causes a shift in profits to the recognition of lower tax rates, thereby reducing the tax paid in Indonesia. This finding emphasizes the need to strengthen supervision of transfer pricing documentation and the implementation of tax regulations consistently. This study provides theoretical and practical contributions to the development of fiscal policy and governance of multinational companies.